FUNGSI DAN PERANAN BATU BERGORES DALAM TRADISI MEGALITIK : STUDI KASUS TEMUAN DI PROVINSI LAMPUNG - Laili, Nurul (Kemendikbud, 2018)
This study puts forward the problems about the function and role of stones in the megalithic tradition. The purpose of this study reveals the existence of scratched stones andtheir role in a megalithic site. The function and role of bergores stones in the Lampung region can not be separated from the element of worship. Scratched stones are always associated with other findings, namely menhirs, dolmen, flat stones, and sequential stones. Desires and expectations from supporters of megalithic culture to gain strength from ancestral spirits treat bergores stone as one of the complementary means of worship other than other types of megaliths. The form of visualization of interactions carried out with ancestral spirits is poured in the form of scratches.